Validating the impact of a molecular subtype in ovarian cancer on outcomes: A study of the OVCAD Consortium - Pils, Dietmar (Cancer Sci, 2012)
Most patients with epithelial ovarian cancer (EOC) are diagnosed at advanced stage and have a poor prognosis. However, a small proportion of these patients will survive, whereas others will die very quickly. Clinicopathological factors do not allow precise identification of these subgroups. Thus, we have validated a molecular subclassification as new prognostic factor in EOC. One hundred and ninety‐four patients with Stage II–IV EOC were characterized by whole‐genome expression profiling of tumor tissues and were classified using a published 112 gene set, derived from an International Federation of Gynecology and Obstetrics (FIGO) stage‐directed supervised classification approach. The 194 tumor samples were classified into two subclasses comprising 95 (Subclass 1) and 99 (Subclass 2) tumors. All nine FIGO II tumors were grouped in Subclass 1 (P = 0.001). Subclass 2 (54% of advanced‐stage tumors) was significantly correlated with peritoneal carcinomatosis and non‐optimal debulking. Patients with Subclass 2 tumors had a worse overall survival for both serous and non‐serous histological subtypes, as revealed by univariate analysis (hazard ratios [HR] of 3.17 and 17.11, respectively; P ≤ 0.001) and in models corrected for relevant clinicopathologic parameters (HR 2.87 and 12.42, respectively; P ≤ 0.023). Significance analysis of microarrays revealed 2082 genes that were differentially expressed in advanced‐grade serous tumors of both subclasses and the focal adhesion pathway as the most deregulated pathway. In the present validation study, we have shown that, in advanced‐stage serous ovarian cancer, two approximately equally large molecular subtypes exist, independent of classical clinocopathological parameters and presenting with highly different whole‐genome expression profiles and a markedly different overall survival. Similar results were obtained in a small cohort of patients with non‐serous tumors. (Cancer Sci 2012; 103: 1334–1341)